Correlation between Gestational Weight Gain in the Second and Third Trimester and Preeclampsia Risk: A Study From Indonesia - Ernawati Ernawati; Lilis Kurniawati; Sri Umijati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Many studies have proposed that pre-pregnancy body mass index and higher gestationalweight gain (GWG) during pregnancy are risk factors for preeclampsia incidence. However, most of thosestudies give attention to total GWG during pregnancy to the risk of preeclampsia, not in a specific trimester.Aim: To examine whether abnormal gestational weight gain in the second and third trimester correlated withthe incidence of preeclampsiaMethods: This cross-sectional study was conducted in a public health centre, in Surabaya, Indonesia,between October 2018 and October 2019. The samples were 63 pregnant women in the second and thirdtrimester. The variable observed was gestational weight gain (GWG) each week during the second and thirdtrimester compared to their pre-pregnancy body mass index (BMI) using the Institute of Medicine (IOM)standards and preeclampsia incidence. Statistical analysis used was Fisher’s Exact Test and Chi-Square Testwith a significance level of 5%.Results: There were 11 and 52 samples in the second and third trimester, respectively. Abnormal weightgain was recorded in 54% of samples in the second trimester and 57% of the preeclampsia third-trimestersamples. Moreover, preeclampsia was diagnosed in 83.3% and 60% samples with abnormal weight gain inthe second trimester and third trimester. Statistical analysis showed abnormal weight gain in the second andthird trimester related to preeclampsia with P-values 0.015 and 0.0001.Conclusion: Abnormal gestational weight gain in the second and third trimester was correlated topreeclampsia.